Pharmacokinetic properties of transdermal flunixin in cattle and its use in pain models - Kleinhenz, Michael Dean (Kansas State University, 2018)
Flunixin meglumine has been used as an antipyretic and anti-inflammatory since the 1980s. In 2013, a novel formulation was released in the European Union for topical administration and transdermal absorption. Approval for transdermal flunixin in cattle in the United States occurred in 2017, and included a label claim for the control of pain associated with infectious pododermatitis (foot rot). This new formulation allows for needle-less delivery of flunixin with minimal restraint and training required. In this dissertation, the pharmacokinetics of transdermal flunixin in Holstein calves at 2 months of age and adult lactating cows is described. In these pharmacokinetic studies, plasma flunixin concentrations were determined using high-pressure liquid chromatography coupled with mass spectroscopy. Pharmacokinetic modeling was completed using non-compartmental modeling methods using a commercially available computer program. Ex vivo prostaglandin E₂ (PGE₂) production using a whole blood model served as a biomarker for the anti-inflammatory effects of flunixin meglumine and suppression of cyclo-oxygenase enzyme-2. The concentrations of PGE₂ were determined using a commercially available enzyme-linked immunosorbent linked assay (ELISA) kit. The effects of age and pain on the pharmacokinetics of flunixin were investigated. Both influenced the pharmacokinetics and anti-inflammatory effects of flunixin. Cautery dehorning without local anesthetic was used in the calf model to generate pain. The pain associated with dehorning caused lower absorption of the transdermal flunixin and a longer terminal half-life. This longer half-life did result in lower PGE₂ concentrations at later time points. The influence of age was determined in the same group of Holstein calves at 2 months and 8 month of age. Age related effects included lower clearance, a longer half-life, and longer suppression of PGE₂ following intravenous injection. Following transdermal administration, older animals had a prolonged absorption leading to a longer half-life and apparent ‘flip-flop’ pharmacokinetics. Additionally, the suppression of PGE₂ was not observed in older calves following transdermal flunixin administration. The analgesic properties of transdermal flunixin were tested using three different pain models. Those pain models include cautery dehorning, surgical castration, and induced lameness. The reduction in plasma cortisol following transdermal administration was the most consistent finding in each model for pain. Infrared thermography (IRT) was used to assess either activation of the autonomic nervous system or local inflammation. Flunixin did not have any effects on substance P concentration in all three pain models. Gait analysis using a floor based pressure mat was used in the assessment of castration and lameness pain. Although there were no observed effects of flunixin in those studies, the use of this technology for pain assessment is promising. Future studies of transdermal flunixin to determine its utility as part of a multi-modal analgesic plan are still warranted. Specifically, the use a of a local anesthetic block at the time of cautery dehorning, as flunixin has minimal effects on pain, and its pharmacokinetics were altered by the painful stimulus. Timing of the dose relative to the painful procedure is also needed as flunixin is rapidly absorbed. Field studies in lame cattle are needed as there is a deficiency in the literature as only models of lameness induction have been reported.
Keywords: Flunixin; Cattle; Pharmacokinetics; Castration; Dehorn; Lameness